Metalinguistic Attention and Punctuation - K. Ya. Seagal (Научный диалог)
This article offers an analysis of the phenomenon of metalinguistic attention in relation to the punctuation marking of compound sentences with a common secondary element (determinant) expressing conjunctive relations. The research material consists of a microcorpus compiled by selectively extracting texts mainly from Russian fiction prose of the 20th21st centuries. The relevance of the study lies in the fact that in contemporary punctuation theory, which increasingly draws on research on metalinguistic operations, the question of metalinguistic attention and its involvement in punctuation marking has not yet been discussed. It is clarified that metalinguistic attention represents a focus on a specific object and its inclusion in the act of metalinguistic reflection. Metalinguistic attention is characterized by its directedness towards activity with the object, its arbitrariness, distributed nature, and reliance on apperception. In the process of punctuation marking, metalinguistic attention performs prognostic and controlling functions. It is demonstrated that in the punctuation marking of compound sentences with a common secondary element (determinant), metalinguistic attention is focused on their individual constituents (common element and linking means) on the one hand, and their structural-semantic integrity on the other.